2022
DOI: 10.1177/03913988211073812
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the timing and intensity of treatment on septic shock patients treated with CytoSorb®: Clinical experience

Abstract: Introduction: A group of adult septic shock patients treated with hemoperfusion (HA) with the Cytosorb® associated with CVVHD were studied to determine (a) the effects of this technique on different clinical variables; and (b) the impact of the pre CytoSorb® interval and its intensity on the outcome. Methods: The catecholamine index (CI) and the pressure-catecholamine Index (PCAI) were used to assess the amount of catecholamine administered at baseline and during the procedure, respectively. The pre-treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The analysis showed that CytoSorb ® treatment was linked with improved survival rates in critically ill COVID-19 patients who received extracorporeal membrane oxygenation. Earlier changes might ensure an ongoing high removal capacity of the adsorber avoiding early saturation in situation with a high cytokine load for the device[ 22 ]. Therefore, a change of adsorber might be appropriate anytime between 6-24 h. It was discussed that it does not need to be changed earlier than 6 h as the device would work properly but a change should not occur later than 24 h to comply with the current IFU, also as no significant removal capacity beyond this point should be expected from the adsorber.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis showed that CytoSorb ® treatment was linked with improved survival rates in critically ill COVID-19 patients who received extracorporeal membrane oxygenation. Earlier changes might ensure an ongoing high removal capacity of the adsorber avoiding early saturation in situation with a high cytokine load for the device[ 22 ]. Therefore, a change of adsorber might be appropriate anytime between 6-24 h. It was discussed that it does not need to be changed earlier than 6 h as the device would work properly but a change should not occur later than 24 h to comply with the current IFU, also as no significant removal capacity beyond this point should be expected from the adsorber.…”
Section: Resultsmentioning
confidence: 99%
“…As in studies evaluating CytoSorb use in the adult population, early initiation of treatment ( 13 , 37 ) and a large number of sessions ( 38 ) appeared to be the optimal setting for such therapy. In our cohort, therapy was initiated within 24 h from the onset of septic shock; this is not always feasible in randomized trials, as the need for written consent often delays the initiation of therapy beyond 48–72 h from the onset of shock.…”
Section: Discussionmentioning
confidence: 99%
“…Removal of cytokines by hemoadsorption in patients with sepsis or systemic inflammatory response syndrome has recently gained increased interest in cardiac surgery [ 1 ]. However, patient selection and timing of application have become very important in this adjunctive therapeutic strategy [ 2 ]. In the current case, a severe systemic inflammatory response with significant clinical deterioration occurred directly after induction of anaesthesia triggering the decision to initiate intraoperative hemoadsorption once the patient was placed on CPB.…”
Section: Discussionmentioning
confidence: 99%
“…More evidence is needed to better define the value of hemoadsorption in cardiac surgery especially relating to appropriate patient selection and timing and dosing of application [ 2 , 5 ]. In 2016, Bernardi et al evaluated intraoperative hemoadsorption in elective CABG patients with no differences in regard to cytokine release [ 6 ].…”
Section: Discussionmentioning
confidence: 99%